A comprehensive review of the theoretical approaches for the airfoil design of lift-type vertical axis wind turbine. (November 2015) - Chen, Jian; Yang, Hongxing; Yang, Mo; Xu, Hongtao; Hu, Zuohuan
Abstract: The airfoil researches of the Darrieus wind turbine will not only affect the power coefficient ( C P ), but also has great impact on the rotor׳s starting ability. A review on a wide number of different design approaches is conducted in this work to change the current situation in which the airfoil research of Darrieus rotor is not sufficient both in depth and in width. Different from the previous review work, this paper not only gives a comprehensive review of the current Darrieus airfoil׳s research approaches but also discussed the applicability of their design processes based on research topics, especially for the approaches based on Panel and the CFD method. Two ways of building airfoil database and current progress of the approach based on Momentum, Vortex and Cascade are addressed. In the end, two promising inverse approaches are proposed for the future study of the Darrieus airfoil. Thus, the aim of this paper is to guide relevant readers and experts to find a proper airfoil design approach considering the research purposes, applicability of design approach based on different theoretical methods and adaptability of design approaches׳ processes.